Social Dominance Orientation, Right-Wing Authoritarianism, and Willingness to Help Addicted Individuals: The Role of Responsibility Judgments - Torleif Halkjelsvik; Jostein Rise (Europe's Journal of Psychology, 2014)
We investigated how Social Dominance Orientation (SDO) and Right Wing Authoritarianism (RWA) were related to motivation to personally help addicted individuals and approval of public spending on addiction treatment. The study employs an attributional analysis based on Weiner’s theory of social motivation. SDO was associated with less approval of public spending on treatment and lower motivation to personally help. RWA was associated with less approval of public spending but exerted a direct positive effect on motivation to personally help. However, the latter effect was cancelled out by an indirect negative effect from an attributional process where addicted individuals were perceived as more responsible for their condition. An association between RWA and judgments of responsibility was further indicated in an investigation of positive vs. negative outcomes of addictions. RWA correlated with ratings of personal responsibility across the valence of outcomes, whereas SDO did not. In conclusion, the relation between RWA and (lack of) motivation to help is partly explained by a greater emphasis on personal responsibility, and the relation between SDO and (lack of) motivation to help is independent of responsibility judgments.